2013
DOI: 10.1007/s00442-013-2664-1
|View full text |Cite
|
Sign up to set email alerts
|

Sex-biased parasitism is not universal: evidence from rodent–flea associations from three biomes

Abstract: The distribution of parasites among individual hosts is characterised by high variability that is believed to be a result of variations in host traits. To find general patterns of host traits affecting parasite abundance, we studied flea infestation of nine rodent species from three different biomes (temperate zone of central Europe, desert of Middle East and tropics of East Africa). We tested for independent and interactive effects of host sex and body mass on the number of fleas harboured by an individual ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
68
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 72 publications
7
68
4
Order By: Relevance
“…This may be due in part to body size differences, with larger males providing a larger food resource, but it has also been attributed to differences in immune function (caused by androgen immune suppression), grooming patterns, movement, and social contact patterns (Perez-Orella and SchulteHostedde, 2005;Krasnov et al, 2012). Yet, many other studies have failed to find sex-biased parasitism, or they have found that sex-biased parasitism varies based on parasite examined (Krasnov Kiffner et al, 2013;Waterman et al, 2013). No evidence of sex-biased parasitism across all flea species was found in this study, even when we included size and sex interaction.…”
Section: Across Individualscontrasting
confidence: 71%
See 1 more Smart Citation
“…This may be due in part to body size differences, with larger males providing a larger food resource, but it has also been attributed to differences in immune function (caused by androgen immune suppression), grooming patterns, movement, and social contact patterns (Perez-Orella and SchulteHostedde, 2005;Krasnov et al, 2012). Yet, many other studies have failed to find sex-biased parasitism, or they have found that sex-biased parasitism varies based on parasite examined (Krasnov Kiffner et al, 2013;Waterman et al, 2013). No evidence of sex-biased parasitism across all flea species was found in this study, even when we included size and sex interaction.…”
Section: Across Individualscontrasting
confidence: 71%
“…Many factors have been postulated to affect prevalence and intensity of flea parasitism among and within host species (Krasnov et al, 2002c;Whiteman and Parker, 2004;Krasnov et al, 2005;Kiffner et al, 2013). Most factors fall broadly into 2 categories: host factors and environmental factors.…”
mentioning
confidence: 99%
“…It is surprising however, that this was not apparent for R. warburtoni/arnoldi as higher R.warburtoni burdens have been recorded during the breeding season (August-March) on male sengis at other localities (Lutermann et al 2012b). However, sex-biased parasitism is far from universal and may vary among parasite species infesting the same host as well as within the same parasite species when infesting different hosts (Scantlebury et al 2010;Kiffner et al 2013). Unexpectedly the abundance of R. distinctus was female-biased and the causes for this are not immediately obvious.…”
Section: Discussionmentioning
confidence: 99%
“…Sex-specific investment strategies in reproduction may account for gender biases in parasite burdens Kiffner et al 2013). This could be due to differences in body size, behaviour and/or physiology between the sexes (Moore & Wilson 2002;Klein 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation